ANALISIS PROSES PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SEKOLAH DASAR - Endang Komara; Deding Ishak; Sobari Sobari; Derifa Siti Muthia; Rahayu Dwi Lestari; Apen Agustendra (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the decision-making process of school principals in improving the quality of education in elementary schools, focusing on the stages of decision-making, influencing factors, and their impact on the quality of learning and teacher performance. Research Method: A qualitative approach was used with a case study design conducted at SDN Rancaekek 05 in Bandung Regency. Data were collected through in-depth interviews, non-participant observation, and documentation studies covering the School Work Plan (RKS), School Budget Plan (RKAS), and academic supervision reports. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing, ensuring data validity through triangulation of sources and methods. Research results: show that school principals make decisions through a systematic and data-oriented process, starting from identifying quality issues, collecting and analyzing information, formulating policy alternatives in a participatory manner, making decisions, implementing programs, and conducting ongoing evaluations. Collaborative and evidence-based decisions have been shown to improve teacher performance, enhance the learning process, and create a more conducive school climate.